Effect of Additional Polyethylene Glycol and Citric Acid on Characteristics of NiMo/g-Al2O3 Catalyst in Light Cycle Gas Oil Hydrodesulfurisation - Dede Sukandar; Lailatul Badriyah; Wawan Rustyawan; Adawiah Adawiah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Sulfur is an impurity in diesel that causes low product quality and environmental pollution. Therefore, a catalyst is needed in the profound hydrodesulfurization (HDS) reaction to produce diesel fuel with low sulfur content. The catalyst synthesized in this work was NiMo/g-Al2O3 with the addition of PEG (2%, 4%, 6%) (w/w) and CA (1%, 2%, and 4%) (w/w). The catalyst was synthesized using the dry impregnation method with a metal concentration of 3% NiO and 15% MoO3. The obtained catalysts were characterized using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), and Surface Area Analyzer (SAA). This work acquired the best catalyst characteristics for the HDS process by adding 2% PEG and 1% CA with a concentration of 3.19% NiO and 13.98% MoO3. The surface area, pore volume, and diameter are 181.655 m2/g, 0.50 cm3/g, and 110.51 Å, respectively. The catalyst activity satisfies Euro V standards at 345 ℃ with a sulfur content of 9.55 ppm, and the sulfur conversion (HDS) is 98.75%. The density and cetane index of the obtained diesel fuel was 0.798 g/mL and 53.6, respectively. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).